2023
DOI: 10.1038/s41419-022-05540-y
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA MBOAT2 promotes intrahepatic cholangiocarcinoma progression and lipid metabolism reprogramming by stabilizing PTBP1 to facilitate FASN mRNA cytoplasmic export

Abstract: The carcinogenic role of FASN by regulating lipid metabolism reprogramming has been well-established in multiple tumors. However, whether mechanisms during intrahepatic cholangiocarcinoma (ICC) progression, such as circRNAs, regulate FASN expression remains unknown. Here we demonstrate a lipid metabolism-related circRNA, circMBOAT2 (hsa_circ_0007334 in circBase), frequently upregulated in ICC tissues, and positively correlated with ICC malignant features. CircMBOAT2 knockdown inhibits the growth and metastasis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…This underlined their possible crucial roles in lipid metabolism, a key aspect in the pathogenesis of ICC. For instance, the cholesterol metabolism pathway has been previously linked with the progression of ICC ( Yu et al, 2023 ). High cholesterol levels have been associated with increased ICC risk, and drugs targeting cholesterol metabolism have shown promise in preclinical ICC models.…”
Section: Discussionmentioning
confidence: 99%
“…This underlined their possible crucial roles in lipid metabolism, a key aspect in the pathogenesis of ICC. For instance, the cholesterol metabolism pathway has been previously linked with the progression of ICC ( Yu et al, 2023 ). High cholesterol levels have been associated with increased ICC risk, and drugs targeting cholesterol metabolism have shown promise in preclinical ICC models.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lactate metabolism in tumorigenesis and TIME has been extensively studied in various cancers (Ratter et al 2018 ; Thorn et al 2009 ; Angelin et al 2017 ). However, prior research has predominantly focused on bile acid and lipid metabolism in iCCA (Zhang et al 2020 ; Yu et al 2023 , 2020 ; Martinez et al 2020 ; Herraez et al 2020 ), and the significance of lactate metabolism in iCCA remains largely undetermined. In this study, 27 prognostic-related genes were identified among 284 LMRGs with the univariate Cox regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Circ-MBOAT2 levels up in cholangiocarcinoma (ICC) cells since it can combine with PTBP1 and protect it from degradation through ubiquitin/proteasome. This results in the facilitation of lipid reprogramming in ICC cells [ 131 ]. Wu et al.…”
Section: Circrnas Regulate Cancer Metabolic Reprogrammingmentioning
confidence: 99%